집단지성을 활용한 폴리매스(Polymath) 활동 사례 - 최수영; 구아현; 고호경 (East Asian Mathematical Journal, 2021)
Education for the future society should emphasize the experience of sharing, coexisting, and solving problems in cooperation with each other in the community. Accordingly, in addition to the problem-solving capability, which is the ultimate goal of mathematics education, it is necessary to strengthen the capability to solve unstructured problems through collaboration. This study attempted to suggest that solving complex problems through collaboration is used in school classes or gifted education by introducing polymath that solves problems using collective intelligence. Accordingly, a target problem was set and an example of polymath in which community members exert each other's intelligence to solve the problem. In addition, by investigating the perceptions of students who have experienced polymath, positive aspects and improvements of polymath were suggested. Through this, this study can contribute to revitalization of mathematics teaching and learning methods using collective intelligence.
Keywords: polymath; collective intelligence; collaboration problem solving